HUMANIZATION OF EDUCATION: ANALYSIS OF THE PROPHET'S INTERACTION WITH THE BEDOUIN - Nasirudin, Nasirudin; Hadjar, Ibnu; Soebahar, Moh. Erfan; Kunaepi, Aang (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Dehumanization such as acts of violence both verbal and non-verbal often occur in educational institutions. Verbal violence such as words that contain insults and harassment. Non-verbal violence such as sexual violence and bullying, especially to those who have deficiencies, both physically and intellectually . This paper aims to analyze the humanization side of the Prophet in interacting with Bedouin people which is identical to the simplicity of thinking. The hadith about the interaction between the prophet and the Bedouin documented in the hadith books were analyzed descriptively. The Prophet's interaction with the Bedouin gave an educational message that responded to feelings , appreciated and adapted the contents of the child's frame of mind. The interaction of the Prophet with the Bedouins deserves to be a model of humanist education. Therefore, Islamic education can adopt the educational practices of the Prophet. This research needs to be developed to find deeper and broader prophetic educational practices.